Breast Density and Risk of Interval Cancers: The Effect of Annual Versus Biennial Screening Mammography Policies in Canada. Issue 1 (February 2022) - Seely, Jean Morag; Peddle, Susan Elizabeth; Yang, Huiming; Chiarelli, Anna M.; McCallum, Megan; Narasimhan, Gopinath; Zakaria, Dianne; Earle, Craig C.; Fung, Sharon; Bryant, Heather; Nicholson, Erika; Politis, Chris; et al.
Regular screening mammography reduces breast cancer mortality. However, in women with dense breasts, the performance of screening mammography is reduced, which is reflected in higher interval cancer rates (ICR). In Canada, population-based screening mammography programs generally screen women biennially; however, some provinces and territories offer annual mammography for women with dense breast tissue routinely and/or on recommendation of the radiologist. This study compared the ICRs in those breast screening programs with a policy of annual vs. those with biennial screening for women with dense breasts. Among 148, 575 women with dense breasts screened between 2008 to 2010, there were 288 invasive interval breast cancers; screening programs with policies offering annual screening for women with dense breasts had fewer interval cancers 63/70, 814 (ICR 0.89/1000, 95% CI: 0.67-1.11) compared with those with policies of usual biennial screening 225/77, 761 (ICR 1.45 /1000 (annualized), 95% CI: 1.19-1.72) i.e. 63% higher (p = 0.0016). In screening programs where radiologists' screening recommendations were able to be analyzed, a total of 76, 103 women were screened, with 87 interval cancers; the ICR was lower for recommended annual (65/69, 650, ICR 0.93/1000, 95% CI: 0.71, 1.16) versus recommended biennial screening (22/6, 453, ICR 1.70/1000 (annualized), 95%CI: 0.70, 2.71)(p = 0.0605). Screening program policies of annual as compared with biennial screening in women with dense breasts had the greatest impact on reducing interval cancer rates. We review our results in the context of current dense breast notification in Canada.